Study of correlation between maternal and cord blood vitamin D3 levels - Rai, Sunil; Das, Saurav; Narayan, Shankar (International Journal of Contemporary Pediatrics, 2019)
Background: Vitamin D deficiency during pregnancy and in newborn period is common in this country. Vitamin D status of the mother is known to influence the vitamin D levels in the neonate, however how closely the maternal vitamin D level correlates with the cord blood Vitamin D is not clearly understood. To study the correlation between maternal and neonatal serum Vitamin D3 levels by as indicated by cord blood 25(OH)D levels and find out if there is a significant variation of cord blood 25(OH)D levels in Vitamin D sufficient and insufficient mothers. Methods: Healthy pregnant women between 18-45 years of age with no known history of chronic disease or long-term medication, consenting for the study were enrolled. Maternal blood sample was collected in peripartum period, cord blood sample was obtained after delivery from the umbilical cord after clamping. Vitamin D3 levels were measured by RIA and paired maternal and cord blood levels were statistically analyzed. Results: 569 paired samples of maternal and cord blood were analyzed. The mean maternal serum 25(OH)D level was 35.63ng/ml (sd 6.18, range 9.2-39.8) as compared to 13.52ng/ml (sd 3.79, range 7.9-27) for the neonates. 457 of the mothers were found to have sufficient, 101(18%) insufficient and 11(2%) deficient Vitamin D levels as per Endocrinological Society guidelines. In comparison, 535(94%) of the neonates had deficient levels, none of the neonates had sufficient Vitamin D levels, 34(5.99%) had insufficient levels. No significant correlation was found between maternal and neonatal serum vitamin 25(OH)D levels (r=0.007, P=0.85). Conclusions: Maternal and Cord blood serum Vitamin D3 levels were found to be poorly correlated in this study.